Secondary prevention of latex allergy. Issue 4 (August 2022) - Nettis, Eustachio; Casella, Rossella; Incorvaia, Cristoforo; Miniello, Andrea
Abstract : Purpose of review: The present review addresses the secondary prevention in healthcare worker, healthcare setting, and in patients outside the healthcare setting. Recent findings: There is sufficient knowledge of the broad aetiology of latex allergy for secondary preventive programmes to be widely adopted. Currently, avoidance of latex-containing surgical products is mandatory in the care of sensitized patients. They should also have a list of occult sources of natural rubber latex exposure and cross-reacting fruits. During all health-care procedures latex allergic patients should be treated in a 'latex-free' environment. Specific sublingual immunotherapy has been suggested as a suitable therapeutic option. It can be offered, in addition to symptomatic treatment, to selected patients, when avoidance measures are not feasible or effective. The use of omalizumab could also be extended as an adjunct to latex immunotherapy. Summary: Despite of the progress made in the secondary prevention of latex allergy, the disease still continues to be a global health problem.